Direct Current (DC) vs Alternating Current (AC) Financial Transaction Flow in Holding and Non-Holding Companies - Fikri, M. Ali; Inapty, Biana Adha; Astuti, Baiq Rosyida Dwi (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
A study on the flow of financial transactions needs to be carried out considering that activities in the financial sector require quick and relevant decisions. The flow of financial transactions in the business world is almost similar to direct current (DC) and alternating current (AC). The phenomenon is that many business people want their funds to be spread outside the company, and some want their funds to only revolve around the company. This study tries to analyze the results of investment flows of funds outside the company and within the company in the scope of the Indonesian capital market. This research is a research using a descriptive approach. The descriptive approach is intended to describe phenomena that occur in the field. The number of sample companies is 175 companies (holding and non-holding). Each company is given a code (code 1 for holding, and code 0 for non-holding), and company data is screened according to research needs on aspects; profit return, stock return, stock price, and profit and loss. Data mining in the field is carried out by researchers by means of secondary data analysis techniques for the capital market through analysis of financial statements from the side of the transaction flow. Then the results of the analysis of the company's flow of funds are processed, compared, and used as the basis for drawing conclusions. The results provide evidence that holding financial flows are more profitable than non-holding according to AC/DC transaction flows. This is in accordance with the risk reduction theory that many developed countries do by controlling the circulation of money only around their country. Theoretically, the results of this study contribute that holding companies have advantages over non-holdings, and practically this research provides a discourse for business people that it is better to run the business alone and not depend on outside parties.